SOSIALISASI SHOPEE SELLER DI PKK RT. 07 DESA TURUNAN KEC. SUSUKAN: ETIKA BERDAGANG RASULULLAH SAW - Saputri, luthfiah Arya; Anis. H, Nazila; Nurfaridah, Didah; Astuti, Yuni (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity was carried out in Derivan RT Hamlet. 07, Susukan District, Semarang Regency with a focus on socialization and introduction to the use of Shopee Seller for PKK mothers. The background to this activity is based on the rapid development of technology and e-commerce in Indonesia, as well as the potential of the local community, the majority of whom work as farmers and traders but have not maximized the use of technology in their economic activities. This program was implemented on August 6 2024 with a direct approach to the community, including education about the development of online buying and selling, how to register and use the Shopee Seller application, as well as interactive discussions with participants. Through this activity, it is hoped that PKK mothers can increase their family's productivity and economic welfare by optimally utilizing the e-commerce platform.